Cover Picture: Synthesis, Crystal Structure, and Characterization of Two Novel One‐ and Two‐Dimensionally Polymeric Copper(II) Phosphonoacetates (Z. Anorg. Allg. Chem. 3/2017). Issue 3 (February 2017) - Köferstein, Roberto; Arnold, Michael; Robl, Christian
Abstract : The cover picture shows sections of the crystal structures of Cu[µ2 ‐OOC(CH2 )PO3 H]·2H2 O (1 ) and Cu1.5 [µ3 ‐OOC(CH2 )PO3 ]·5H2 O (2 ). (1 ) is a layer‐like coordination polymer, which due to its ‐PO3 H group can be regarded as the protonated form of a cation exchanger. The density of negative charge of the deprotonated layers would be similar to that of layered silicate minerals. The diffuse reflectance UV/Vis spectrum of powdered (1 ) can be fitted well by three Gaussian curves. (2 ) has polyanionic chains with {Cu(H2 O)[OOC(CH2 )PO3 ]}n n– composition. Hydrated Cu 2+ cations are accommodated between the chains as counter ions and therefore (2 ) can be regarded as a chain‐like cation exchanger loaded with [Cu(H2 O)6 ] 2+ . (2 ) shows antiferromagnetic coupling at low temperature obviously caused by a super‐superexchange mechanism. More details are discussed in the article by R. Köferstein, M. Arnold, and C. Robl on page276 ff.